Structure and cognition aspects of Hindu caste and ritual - Das, Veena (New Delhi ; Oxford : Oxford University Press, 2012)
Sociological analysis of Hindu caste & ritual has primarily been confined to the empirical study of local communities. In this work the author adds a new dimension by basing her data on an examination of selected myths in Puranic & Sutra literature, in particular the Dharmaranya Purana & the Grihya Sutra.
Description based on online resource; title from PDF title page (viewed on Aug. 15, 2012).
Keywords: Caste -- India; Hinduism -- Rituals; x; Puranas. -- Criticism, interpretation, etc